2017
DOI: 10.1109/tcyb.2017.2655054
|View full text |Cite
|
Sign up to set email alerts
|

Output Feedback Distributed Containment Control for High-Order Nonlinear Multiagent Systems

Abstract: In this paper, we study the problem of output feedback distributed containment control for a class of high-order nonlinear multiagent systems under a fixed undirected graph and a fixed directed graph, respectively. Only the output signals of the systems can be measured. The novel reduced order dynamic gain observer is constructed to estimate the unmeasured state variables of the system with the less conservative condition on nonlinear terms than traditional Lipschitz one. Via the backstepping method, output fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…, N + M. Remark 1. In the literature [7,24], it is assumed that the MASs will not show actuator faults at any time. However, due to machine aging or working environment, actuator faults are inevitable in actual industrial production.…”
Section: Problem Description and Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…, N + M. Remark 1. In the literature [7,24], it is assumed that the MASs will not show actuator faults at any time. However, due to machine aging or working environment, actuator faults are inevitable in actual industrial production.…”
Section: Problem Description and Preliminariesmentioning
confidence: 99%
“…In fact, nonlinear systems can better describe a practical engineering problem than linear systems, such as manipulator systems [19], inverted pendulum systems [20], and rigid robotic systems [21]. All systems models in [16][17][18] and practical application systems models in [19][20][21][22][23][24][25][26] are first-or second-order systems. For example, under the common assumption that each agent can only obtain the relative information of its neighbours intermittently, the containment control method was proposed for a class of second-order MASs with inherent nonlinear dynamics in [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further study of the cooperative control problem of multiagent systems, extending the consensus control of a single leader, considers multiagent cooperative control in the case of multiple leaders, and designs a controller to make the followers converge to a convex hull composed of multiple leaders, which is called containment control. As a special case of cooperative control, many research results of MASs containment control have been reported in the field of integer order control, such as adaptive control [12,13], feedback control [14,15], linear matrix inequalities (LMIs) [16,17], sliding mode control [18], and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high-order nonlinear systems have been universally studied. For example, [32,33] investigated containment problems and consensus problems of high-order nonlinear systems, respectively. However, to the best of our knowledge, there are no results about noncooperative games of high-order nonlinear multi-agent systems over weight-unbalanced digraphs.…”
Section: Introductionmentioning
confidence: 99%